A review of functionalized carbon nanotubes and graphene for heavy metal adsorption from water: Preparation, application, and mechanism. (March 2018) - Xu, Jiang; Cao, Zhen; Zhang, Yilin; Yuan, Zilin; Lou, Zimo; Xu, Xinhua; Wang, Xiangke
Abstract: Carbon-based nanomaterials, especially carbon nanotubes and graphene, have drawn wide attention in recent years as novel materials for environmental applications. Notably, the functionalized derivatives of carbon nanotubes and graphene with high surface area and adsorption sites are proposed to remove heavy metals via adsorption, addressing the pressing pollution of heavy metal. This critical revies assesses the recent development of various functionalized carbon nanotubes and graphene that are used to remove heavy metals from contaminated water, including the preparation and characterization methods of functionalized carbon nanotubes and graphene, their applications for heavy metal adsorption, effects of water chemistry on the adsorption capacity, and decontamination mechanism. Future research directions have also been proposed with the goal of further improving their adsorption performance, the feasibility of industrial applications, and better simulating adsorption mechanisms. Graphical abstract: Highlights: Removal of heavy metals from water has drawn wide attention. Various functionalized carbon nanotube and graphene nanomaterials were stated. Effects of water environmental chemistry on heavy metals removal were discussed. Adsorption isotherms, kinetics, thermodynamics, and pathways were discussed. Some research prospects were proposed for future studies and application.